Influence of Cold Work on Pitting Corrosion and Cavitation Erosion of High Interstitial FeCrMnCN Austenites. Issue 12 (23rd February 2015) - Niederhofer, Philipp; Siebert, Sabine; Huth, Stephan; Theisen, Werner; Berns, Hans
Abstract : High interstitial steels (HIS) are based on the joint addition of carbon and nitrogen, which resulted in an austenitic FeCrMn steel grade. In contrast to high nitrogen steels (HNS), they can be produced by conventional metallurgy and offer a unique combination of mechanical properties and corrosion resistance. This makes them promising candidates for the use in environments featuring corrosive or wear attack or even both. Corrosion resistance can be improved by the addition of molybdenum, particularly in the case of media containing chloride ions. In this study, different FeCrMnCN alloys were investigated by means of pitting corrosion testing in sodium chloride solution, as well as cavitation erosion resistance. These properties were examined depending on prestraining, since the latter is used to strengthen this kind of alloys. Abstract : High interstitial austenitic stainless steels offer a unique combination of mechanical properties and corrosion resistance. Their mechanical properties can even be improved by cold working. In this study different FeCrMnCN alloys are investigated by means of pitting corrosion and cavitation testing. The results show higher cavitation resistance and no significant deterioration of corrosion properties due to the prestraining.